Charge distribution and calcium affinity of sulfated alpha-L-galactans from ascidians. Comparison between linear and highly branched polymers - Ruggiero, J.; Fossey, Marcelo Andrés [UNESP]; Santos, J. A.; Mourao, P. A. S. (Elsevier B.V., 1998)
Calcium binding and charge distribution on highly branched and linear sulfated L-galactans from ascidians have been studied using a metallochromic indicator and conductimetric titrations. The distance between charged groups of the linear and highly branched galactans does not vary despite their marked differences in sulfate/total sugar molar ratios. These results indicate that the sulfated L-galactose units are concentrated in the central polysaccharide core and not intercalated among non-sulfated units. This inference is consistent with the chemical studies of these galactans. Surprisingly, calcium affinity increases with increasing amounts of non-sulfated sugar branches in the molecule. Thus, calcium binding in these polymers is not a simple function of availability of anion binding sites but a more complex calcium-polysaccharide interaction. (C) 1998 Elsevier B.V. Ltd. All rights reserved.